Determination of the critical stress for the initiation of dynamic transformation in commercially pure titanium. (May 2017) - Aranas, Clodualdo; Foul, Anes; Guo, Baoqi; Fall, Ameth; Jahazi, Mohammad; Jonas, John J.
Abstract: The dynamic transformation of alpha to beta is shown to take place in titanium at temperatures below the beta transus. The driving force for this transformation is the net softening associated with the formation of the lower flow stress beta phase. The obstacle to the transformation consists of the free energy difference between the phases as well as the work of dilatation during the phase change. Here the critical condition for transformation is defined as the moment when the driving force becomes equal to the obstacle energy. This approach is supported by data obtained from compression tests. Graphical abstract: